2014
DOI: 10.1111/ijd.12686
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dermoscopic evaluation of cutaneous leishmaniasis

Abstract: When the findings obtained in this study were evaluated along with those reported in the literature, it became apparent that follicular plugs, also called "teardrop-like structures", seen on the face and neck may be a dermoscopic feature specific to CL. As hairpin-like vessels seen in an asymmetric radial arrangement were often observed on parts of the body other than the face, further dermoscopic studies comparing the lesions of CL with other ulcerating lesions are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
2
23
1
Order By: Relevance
“…In Turkey, Ayhan et al [5] found that the vascular structures observed on dermoscopy were most commonly polymorphic vessels, followed by hairpin-like and arborizing vessels. The most common nonvascular structure was erythema, followed by crusting, erosion/ulceration, and teardrop-like structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Turkey, Ayhan et al [5] found that the vascular structures observed on dermoscopy were most commonly polymorphic vessels, followed by hairpin-like and arborizing vessels. The most common nonvascular structure was erythema, followed by crusting, erosion/ulceration, and teardrop-like structures.…”
Section: Discussionmentioning
confidence: 99%
“…The most common nonvascular structure was erythema, followed by crusting, erosion/ulceration, and teardrop-like structures. They concluded that teardrop-like structures may be specific to leishmaniasis localized on the face and neck [5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A polymorphous vascular pattern, composed of two or more different vascular patterns, can be a dermoscopic sign for malignant skin lesions and especially melanoma (7). It can also be seen in benign skin lesions such as eccrine poroma and cutaneous leishmaniasis (8,9). We observed polymorphous vessels including coiled, punctate and looped vessels in our case, indicating that cutaneous sporotrichosis is another skin disease that can display a polymorphous vascular pattern.…”
Section: Discussionmentioning
confidence: 99%